Palunad a proposed mobile application aimed to legitimize the shared mobility services of the Bicolano drivers for commuters along the Bicol-Quezon City routes - Esmeria, Amanda Beatrice R.; Dans, Sandra Michelle (Quezon City College of Fine Arts, University of the Philippines Diliman, 2023)
The public transportation system in the Philippines has long been inadequate and commuting has always been tough. When CoViD-19 hit in early 2020, lockdowns disrupted public transportation even further, and a population of commuters to and from Bicol and Quezon City were greatly affected. As a result of the limited availability of transport, unauthorized transport vehicles operating without a valid franchise increased in number. This door-to-door shared mobility services served commuters along the Bicol-Q.C. routes and have continued to ferry passengers from 2020 to 2023 despite the gradual normalization of provincial public transportation.

This research explores the experiences of the Bicolano private car owners who drove colorum transportation vehicles along the Bicol-Quezon City routes during the pandemic, and the commuters that used these private door-to-door transportation services. This study aims to increase our understanding of why colorum vehicles with Bicol-Quezon City routes persist, and why commuters continue patronizing them. The government's action to conduct anti-colorum campaigns resulted in many apprehensions that was not able to address the root of the problem.

This research proposes a shared mobility service through a mobile application that can help legitimize the drivers' service for this certain commuter population, and help bridge gaps in transportation especially rural areas.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography: leaves 95-99
Keywords: Public transport system -- Philippines; Transportations -- Philippines; Transportations -- Door-to-door services -- Philippines